2001
DOI: 10.1164/ajrccm.164.5.2008003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidant Supplementation on Ozone-Induced Lung Injury in Human Subjects

Abstract: To determine whether antioxidants can influence human susceptibility to ozone (O(3))-induced changes in lung function and airway inflammation, we placed 31 healthy nonsmoking adults (18 to 35 yr old) on a diet low in ascorbate for 3 wk. At 1 wk, subjects were exposed to filtered air for 2 h while exercising (20 L/min/m(2)), and then underwent bronchoalveolar lavage (BAL) and were randomly assigned to receive either a placebo or 250 mg of vitamin C, 50 IU of alpha-tocopherol, and 12 oz of vegetable cocktail dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 41 publications
5
123
0
1
Order By: Relevance
“…) following placebo and vitamin supplementation (250 mg vitamin C, 50 IU (33 mg) vitamin E, and a 12 oz vegetable cocktail rich in carotenoids, daily for 14 days) [41]. In this study a small, yet significant blunting of the ozone-induced decrement in FEV1 (p=0.05) was observed in the supplemented group with a similar trend (p=0.06) observed in the FVC response.…”
Section: Respiratory Tract Lining Fluid Antioxidants and Air Pollutionsupporting
confidence: 69%
“…) following placebo and vitamin supplementation (250 mg vitamin C, 50 IU (33 mg) vitamin E, and a 12 oz vegetable cocktail rich in carotenoids, daily for 14 days) [41]. In this study a small, yet significant blunting of the ozone-induced decrement in FEV1 (p=0.05) was observed in the supplemented group with a similar trend (p=0.06) observed in the FVC response.…”
Section: Respiratory Tract Lining Fluid Antioxidants and Air Pollutionsupporting
confidence: 69%
“…SAMET et al [91] observed no difference in the bronchoalveolar lavage content of polynuclear cells and other inflammatory markers between supplement and placebo groups after O 3 challenge. Similarly, Mudway et al [92] reported no effect of supplementation with vitamin C and vitamin E on O 3 -induced neutrophilia in healthy individuals responsive to O 3 .…”
Section: Inflammatory Responsementioning
confidence: 95%
“…In a study of asthmatic adults, a cocktail of vitamin C (500 mg) and vitamin E (400 UI) protected against a decrease in peak expiratory flow from SO 2 challenge after O 3 exposure [90]. In another study [91], subjects were first deprived of vitamin C and then supplemented with a relatively low dose of vitamin C (250 mg), vitamin E (100 mg) and vegetable cocktail. Supplementation protected against acute change in lung function (forced expiratory volume in one second and forced vital capacity) after O 3 challenge.…”
Section: Antioxidant Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The main results of the original study revealed that supplemental dietary antioxidants protected human subjects from the adverse effects of O 3 inhalation on lung function and have been published elsewhere (Samet et al, 2001).…”
Section: Methodsmentioning
confidence: 99%